Muslims, Christians, and the challenge of interfaith dialogue - Smith, Jane I. (Oxford University Press, 2007)
Introduction -- Encountering each other -- The legacy of engagement -- Islam: a truly American religion? -- Models of Christian-Muslim dialogue in America -- When dialogue goes wrong -- The pluralist imperative: Christian perspectives -- The pluralist imperative: Muslim perspectives -- New directions in dialogue